The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.4149/neo_2020_190908n882
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sarcopenia, hypoalbuminemia, and laparoscopic surgery on postoperative complications in elderly patients with colorectal cancer: A prospective study

Abstract: With the increasing number of elderly patients, the risk of diseases such as colorectal cancer (CRC) has increased. The objective of this prospective study was to explore the effects of sarcopenia, hypoalbuminemia, and laparoscopic surgery on postoperative complications among elderly patients who recently underwent colorectal surgery. Patients aged over 65 years who underwent surgery for CRC at the First Affiliated Hospital of Wenzhou Medical University were considered for this study. The demographical and cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…In the context of CRC, BSA has been characterized as a prognostic factor linked with survival and a predictor of surgical morbidity and death. [6,9,10]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of CRC, BSA has been characterized as a prognostic factor linked with survival and a predictor of surgical morbidity and death. [6,9,10]…”
Section: Introductionmentioning
confidence: 99%
“…In the context of CRC, BSA has been characterized as a prognostic factor linked with survival and a predictor of surgical morbidity and death. [6,9,10] BSA measurement is simple, affordable, accurate, and trustworthy, frequently used to determine patients general state with many types of medical conditions. Consequently, we aimed to evaluate the predictive value of preoperative hypoalbuminemia in patients undergoing colorectal surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigations studying the synergistic impact of sarcopenia and hypoalbuminemia on clinical outcomes have largely been conducted for other clinical applications, yet they report similar findings. 27 , 28 , 29 , 30 Few mechanisms have been proposed that may explain this association. Importantly, both hypoalbuminemia and sarcopenia are associated with chronic diseases and advanced age, as well as each other.…”
Section: Discussionmentioning
confidence: 99%
“…However, the combined effects of hypoalbuminemia and sarcopenia on adverse outcomes have been described in other contexts, such as incident disability, postoperative complications in colorectal cancer and renal cell carcinoma, and survival after infrainguinal revascularization. 27 , 28 , 29 , 30 In the present study, we aimed to investigate the combined effects of LMM as a surrogate for sarcopenia and admission hypoalbuminemia on in‐hospital outcomes of patients with ADHF; we also aimed to study the impact of LMM combined with improvement in albumin during hospitalization or discharge hypoalbuminemia on postdischarge outcomes.…”
mentioning
confidence: 99%
“…[11][12][13][14] Many studies reported that high NLR, low hemoglobin, and low serum albumin levels show an unfavorable prognosis in lung cancer. [15][16][17] Additionally, many studies have shown that blood values such, as white blood cell count, neutrophil count, and NLR, are valuable in predicting prognosis, mortality, complications, and hospital stay in cardiovascular diseases. [18][19][20] We hypothesize that various scoring systems and laboratory parameters may be more effective in predicting PPCs in patients undergoing thoracic surgery.…”
Section: Introductionmentioning
confidence: 99%